Aspectos da cultura da laranja em Bebedouro. - Bray, S. C. (My University, 1980)
Cultivation began in the 1930's but in the 1940's with the market drop, due to the Second World War, the paulista citrus production declined, aggravated by 'tristeza' disease. After 1945 the export market increased and in the 1950's production increased in Bebedouro on many estates due to the emergence of packing-houses. In the 1960's citrus industries (concentrated juice) for export began. Limeira and Bebedouro are the principal producing and exporting centres of citrus products in Brazil. -after English summary
Aspects of orange cultivation in Bebedouro, Sao Paulo, Brazil
Keywords: agriculture; Bebedouro; citrus production; Limeira; South America